Goodness & advice - Thomson, Judith Jarvis (University Center for Human Values series., 2001)
How should we live? What do we owe to other people? In Goodness and Advice, the eminent philosopher Judith Jarvis Thomson explores how we should go about answering such fundamental questions. In doing so, she makes major advances in moral philosophy, pointing to some deep problems for influential moral theories and describing the structure of a new and much more promising theory. Thomson begins by lamenting the prevalence of the idea that there is an unbridgeable gap between fact and value--that to say something is good, for example, is not to state a fact, but to do something more like expres.